Analisis Forecasting Volume Penjualan Produk Indihome PT. Telkom Cabang Tenggarong - Reynaldo, Charazevo; Palinggi, Yonathan (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2020)
The aim of this research is to find out forecasting sales of indihome products, PT. Telkom Tenggarong Branch. The results of the study using the single moving average method of indihome product sales, namely in January sales were 326 units, February as many as 320 unit, March to May as many as 319 units, June and July increased to 320 units, August and September 319 units. Whereas when using the linear trend method sales tend to increase every month. In January, sales of 337 units, in June 370 units, in July as many as 377 units, in August 383 units and months September 390 units. The results showed that the single moving average method with an error rate will be smaller every forecasting done. The results obtained by the single moving average method, indihome product sales volume occurs sales fluctuations. While the linear trend of error rate tend to be constant with the results of the sales volume of indihome products having a positive trend. Keywords : Forecasting, Sales Volume, Single Moving Average